Pengaruh Retribusi Daerah dan Belanja Modal Terhadap Pertumbuhan Ekonomi di Daerah Istimewa Yogyakarta - Solekha, Sheptia Dwi Imroatus; Hanifa, Nurul (Jurnal Ekonomika : INDEPENDEN, 2025)
A region's economic development can be seen from its economic growth. This study aims to look at the effect of regional retrubution and capital expenditure on the economic growth of the Special Region of Yogyakarta vulnerable in 2013-2023. The economic growth in question uses gross regional domestic product at constant prices as an indicator. The study is quantitative, using panel data regression. Utilising data from each district and city sourced from the official website of the Ministry of Finance and the Central Bureau of Statistics as secondary research data processed using Eviews 12. The findings in this study obtained the best regression model with the Fixed Effect Model (FEM). The results found that local retribution on economic growth has no significant effect, capital expenditure on economic growth has a positive effect and is also significant. Simultaneously, each variable affects economic growth.